Characterization of Na+/H+ Exchange in Platelets - Livne, Avinoam; Grinstein, Sergio; Rothstein, Aser (Thrombosis and Haemostasis, 1987)
Acidification of the cytoplasm of human blood platelets leads to activation of Na+/H+ exchange. As a result, alkalinization occurs that is detectable by an intracellular fluorescent pH indicator. The activity of the exchanger can also be measured by the swelling of platelets suspended in Na-propionate medium using a Coulter Counter: the rapid entry of propionic acid leads to acidification and activation of Na+/H+ exchange with the parallel entry of Na+ and propionic acid leading to osmotic swelling. The Na+/H+ exchanger is sensitive to amiloride and to derivatives that are reported to be more specific inhibitors; it is specific for Na+ and Li+ with no measurable transfer of K+, Rb+ or Cs+; its Km for Na+ is 75 to 90 mM; it displays competitive behavior between Na+ and amiloride; its activity is decreased in cells loaded with Na+ by prolonged ouabain treatment; and it has a high temperature coefficient. These properties are in general similar to those of the exchanger in other cells. It is suggested that the Na+/H+ exchanger plays a role in platelet pH regulation.
Keywords: Sodium; proton exchange; Human platelets